Yttrium Doping of Perovskite Oxide La2Ti2O7 Nanosheets for Enhanced Proton Conduction and Gas Sensing Under HighHumidity Levels - Jian Wang; Caicai Sun; Jusheng Bao; Zhiwei Yang; Jian Zhang; Xiao Huang (Sensors)
Water molecules from the environment or human breath are one of the main factors affecting the accuracy, efficiency, and long-term stability of electronic gas sensors. In this contribution, yttrium (Y)-doped La2Ti2O7 (LTO) nanosheets were synthesized by a hydrothermal reaction, demonstrating improved proton conductivity compared to their non-doped counterparts. The response of Y-doped LTO with the optimal doping concentration to 100 ppm NO2 at 43% relative humidity (RH) was −21%, which is four times higher than that of bare La2Ti2O7. As the humidity level increased to 75%, the response of Y-doped LTO further increased to −64%. Unlike the gas doping effect observed in previous studies of semiconducting metal oxides, the sensing mechanism of Y-doped LTO nanosheets is based on the enhanced dissociation of H2O in the presence of target NO2 molecules, leading to the generation of more protons for ion conduction. This also resulted in a greater resistance drop and thus a larger sensing response at elevated humidity levels. Our work demonstrates that proton-conductive oxide materials are promising gas-sensing materials under humid conditions.